E-commerce internationalization for top luxury fashion brands: some emerging strategic issues. Issue 4 (25th February 2020) - Guercini, Simone; Ranfagni, Silvia; Runfola, Andrea
Abstract : Purpose: This article investigates the integration between online and offline channels in the internationalization of top luxury fashion brands. It aims at pointing out the main drivers of such integration, comparing the top international markets for the luxury goods sector. Design/methodology/approach: The empirical investigation regards an analysis on secondary data of eight top luxury players in the fashion industry and 12 top international markets for the luxury goods sector. Findings: This study shows that the integration between physical and online channels is driven by the market rather than by the company strategies. Moreover, it points out that the e-commerce presence of luxury brands is stronger in developed markets, while in emerging markets it is less pronounced. Moreover, the integration between channels is mainly achieved through logistic rather than technological tools. Research limitations/implications: This research has major implications. From the perspectives of luxury brands in the fashion industry, it points out the main drivers for integration between online and offline channels and the main differences among international markets. Practical implications: This research deliver insights for marketers interested in benchmarking with top leading luxury brand in fashion and to define e-commerce internationalization policies. Originality/value: The originality of the article regards the joint consideration of two emerging issues for luxury players, e-commerce internationalization and omnichannel strategies.